Pembelajaran Berbasis Multikultural - Nazila Syifa Thohiroh (MAN Insan Cendekia Jambi, 2024)
Indonesia is a country rich in cultural, ethnic, religious, linguistic, and customary diversity. As a nation with more than 17,000 islands and over 300 ethnic groups. However, this diversity can also be the main source of the country's destruction if it is not properly united. Through multicultural-based education, it is hoped that it will be able to foster and nurture the unity and integrity of Indonesia. This paper is written using the literature review method, which is a term referring to a particular research or development methodology carried out by collecting and evaluating related research on a specific topic focus. This research aims to explain multicultural-based education, including its definition, basic principles, and challenges.